Dynamic PET reveals compartmentalized brain and lung tissue antibiotic exposures of tuberculosis drugs - Chen, Xueyi; Arun, Bhavatharini; Nino-Meza, Oscar J.; Sarhan, Mona O.; Singh, Medha; Jeon, Byeonghoon; Mane, Kishor; Shah, Maunank; Tucker, Elizabeth W.; Carroll, Laurence S.; Freundlich, Joel S.; Peloquin, Charles A.; et al. (Nature communications, 2024)
Tuberculosis (TB) remains a leading cause of death, but antibiotic treatments for tuberculous meningitis, the deadliest form of TB, are based on those developed for pulmonary TB and not optimized for brain penetration. Here, we perform first-in-human dynamic 18 F-pretomanid positron emission tomography (PET) in eight human subjects to visualize 18 F-pretomanid biodistribution as concentration-time exposures in multiple compartments (NCT05609552), demonstrating preferential brain versus lung tissue partitioning. Preferential, antibiotic-specific partitioning into brain or lung tissues of several antibiotics, active against multidrug resistant (MDR) Mycobacterium tuberculosis strains, are confirmed in experimentally-infected mice and rabbits, using dynamic PET with chemically identical antibiotic radioanalogs, and postmortem mass spectrometry measurements. PET-facilitated pharmacokinetic modeling predicts human dosing necessary to attain therapeutic brain exposures. These data are used to design optimized, pretomanid-based regimens which are evaluated at human equipotent dosing in a mouse model of TB meningitis, demonstrating excellent bactericidal activity without an increase in intracerebral inflammation or brain injury. Importantly, several antibiotic regimens demonstrate discordant activities in brain and lung tissues in the same animal, correlating with tissue antibiotic exposures. These data provide a mechanistic basis for the compartmentalized activities of antibiotic regimens, with important implications for developing treatments for meningitis and other infections in compartments with unique antibiotic penetration. Antibiotic treatments for tuberculous meningitis, the deadliest form of tuberculosis, are not optimized. Here, PET in human and animal studies is used to measure the biodistribution of several antibiotics to develop optimized regimens for drug-resistant tuberculous meningitis.